Isolation of Nitrogen-Fixing Bacteria from Rhizosphere of Sugarcane Plantation as Candidates for Biofertilizer - Altayib Hasan Mohammed Ahmed Bin Yahmed; Irfan Mustafa; Farida Rahayu (Journal of Experimental Life Science)
Exploration of nitrogen-fixing bacteria as a sustainable alternative to conventional fertilizers is important in agriculture. The study aims to isolate and characterize the potential nitrogen-fixing bacteria (NFB) from soils of several sugarcane fields in East Java. Specifically, the bacteria were isolated from sugarcane fields in Blitar, Ngawi, and Glugur Malang. Soil samples were collected, and NFB were isolated using an Nfb medium. Next, the ability of these isolates to fix nitrogen in a liquid medium was evaluated by measuring the ammonium released after different incubation periods (24, 72, and 120 hours). The study obtained five potential isolates that grew well on the agar medium and changed the medium’s pH. Significant growth and pH increase at the liquid medium were observed across the isolates over time. This rise in pH was not always attributed to the ammonia production by those NFB. Only two isolates released ammonia at detectable concentrations as much as 1.13 mg.L-1 and 1.40 mg.L-1, respectively. Hence, isolates C and D were selected as potential NFB for application in replacing synthetic nitrogen fertilizer.